Grónská cesta k suverenitě: role Evropské unie v tomto procesu - Novotný, Dominik (Univerzita Karlova, Fakulta sociálních věd, 2016)
This thesis researches the role of the European Union in the Greenlandic journey towards economic self-sufficiency and political sovereignty. The main goal of the thesis is to interpret the position of EU as a foreign partner of Nuuk. The author concentrates on three main areas. The first one is fishery, the sector which is currently of the greatest importance to the country's economy and on the grounds of which Greenland left the structures of the European integration. This area was also fundamental for the shaping of the original form of the EU- Greenlandic relations. The second area is the extraction of Greenlandic natural resources, which in future might be the potential source of Greenlandic economic self-sufficiency; however this will not be possible without foreign investments. The third area is the political framework of sovereignty-seeking efforts within the country, the entire Danish realm and in the global context. This paper is a compilation thesis supplemented by author's interpretations of primary sources. In the thesis the author confirms his hypothesis that the EU even after Greenland left the EEC represents a fundamental aspect for the development of Greenland toward full independence. Tato práce zkoumá roli Evropské unie v grónské cestě k ekonomické soběstačnosti a politické suverenitě. Hlavním cílem práce je interpretovat pozici EU, jakožto zahraničního partnera Nuuku. Autor se v práci věnuje třem oblastem. První z nich je rybolov, sektor, který je pro Grónsko momentálně ekonomicky nejvýznamnější a na jehož základě vystoupilo ze struktur evropské integrace. Rybolov byl také zásadní pro nastavení podoby původního vztahu mezi EU a Nuukem. Druhou oblastí je těžba grónského nerostného bohatství, které je do budoucna potenciálním zdrojem grónské ekonomické soběstačnosti, nicméně rozvoj tohoto sektoru nebude možný bez zahraničních investic. Třetí oblastí je politický rámec snah o suverenitu na půdě domácí, v rámci celého Dánského království i na mezinárodním poli. Po metodologické stránce je práce ...